Consumers internet usage and their behaviour to enhance broadband penetration in Sabah - Mohd Hamdan Adnan (Penerbit UMS, 2016)
This study was conducted in 2012 by a team of researchers from the School of Social Science (SSS), Universiti Malaysia Sabah (UMS) to discover the level of broadband penetration in Sabah and the factors hindering or facilitating its growth. At the point of the study, Sabah has the lowest broadband penetration level. The government is trying to increase it reach in the state to make comparable to the other Malaysian states at the very least. An opinion survey was used on 3200 respondents selected randomly covering all the districts in Sabah, both in the urban and rural areas as well as those in the isolated zones. A questionnaire was prepared to gather relevant data to meet the objectives of the study which include the respondents’ awareness of broadband, their attitude towards it, their utilization of it, their expectations of it and the future of broadband in Sabah. The study found that respondents from all areas and walks of life were expecting that the broadband penetration to be quickly expanded and the quality of transmission and service enhanced. Interestingly respondents from the lowest income group were the most claiming they were willing to subscribe to broadband for their own benefits despite their limitations. The study recommendations include getting all the stakeholders together including from the civil society organization to meet the objective of realizing an information culture society in Sabah through full broadband penetration in the state.